WAYS TO INCREASE THE COMPETITIVENESS OF PERSONNEL IN THE LABOR MARKET - Karimov Ilham (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Abstract: In the modern era, the world labor market is undergoing profound changes based on digital technologies, artificial intelligence and automation. As a result, many traditional professions are gradually disappearing, with new types of professions that require digital competencies, flexibility and multifunctional skills developing rapidly. According to the International labour Organization (ILO) forecasts, over 40% of jobs will require advanced digital skills in the coming years. This situation is forcing all countries, including Uzbekistan, to reform the education and professional training system in order to prepare a competitive workforce. The COVID-19 pandemic and the subsequent economic crisis accelerated these changes, leading to shrinking jobs, the spread of remote jobs, and the rise of freelancing. Employers now demand from employees not only knowledge, but also quick learning skills, technological flexibility and mobility. Uzbekistan has implemented significant reforms in recent years to liberalize the labor market, develop non-governmental employment services, and create digital platforms for youth employment. The new Uzbekistan development strategy for 2022-2026 emphasizes the creation of hundreds of thousands of jobs and strengthening the vocational education system as a national priority. Despite these reforms, problems remain Uzbekistan has implemented significant reforms in recent years to liberalize the labor market, develop non-governmental employment services, and create digital platforms for youth employment. The new Uzbekistan development strategy for 2022-2026 emphasizes the creation of hundreds of thousands of jobs and strengthening the vocational education system as a national priority. Despite these reforms, problems remain. A large part of young professionals do not have enough knowledge of modern professions and technologies. The" Education-Skills-Employment " chain is still fragmented and the competitiveness of human resources requires systematic improvement. The international experience demonstrates the importance of dual education, competency-based assessment, and lifelong learning as a means of adapting labor skills to labor market demands.